Climate change, marine pathogens, and human health - Semenza, Jan C.; Hess, Jeremy J.; Provenzano, Daniele (The journal of the American Medical Association, 2025)
The year 2024 was the hottest ever recorded, accompanied by elevated global sea surface temperature, which is the temperature of ocean water close to the surface. Elevated sea surface temperature causes more water to evaporate into the atmosphere, leading to storm clouds, major storms, extreme precipitation, and intensified hurricanes, typhoons, and cyclones. Warming oceans also contribute to declining numbers of fish in global marine fisheries, coral reef degradation, and proliferation of toxic algae, leading to harmful algal blooms. The appearance of harmful algal blooms in freshwater and seawater is affected by multiple processes, including nutrient pollution (an increased load of nutrients that promote rapid organism growth and reproduction), reduced water flow, and ocean acidification. Along the Atlantic and Alaskan coastlines, sea surface temperature increases have been particularly pronounced.